Detection and Quantitation of ß-sitosterol in Clerodendrum infortunatum and Alternanthera sessilis by HPTLC - Gupta, Rajiv; Singh, H. K. (Pharmacognosy Communications)
Introduction: High Performance Thin Layer chromatography is an important tool used qualitatively as well as quantitatively for the purity and identity determinations of crude drugs and one of the major recent advances in the area of standardization, and also to keep a check on adulteration. Methods: In the present study High Performance Thin Layer Chromatography has been developed for detection, and quantification of ß-sitosterol in the leaves of Clerodendrum infortunatum and Alternanthera sessilis. Increasing serial dilutions of reference standard ß-sitosterol (200 to 1000 μg mL-1) were scanned at 273 nm to detect and quantify the concentrations of ß-sitosterol in the test samples. Results: The estimated values obtained from the same were 934.18 and 912.80 μg mL-1 for Clerodendrum infortunatum and Alternanthera sessilis respectively. The presence of the biomarker- i.e. ß-sitosterol in appreciable amounts shows sufficient scientific promise in both these plants as a good source of the same. Conclusion: The method provided a rapid and easy approach for detection and the quantitation of the bio-marker ß-sitosterol. The authors also aim to validate the present method in terms of ruggedness and accuracy and undertake the isolation of ß-sitosterol from the said plant.
Keywords: Clerodendrum infortunatum; Bhant; Alternanthera sessilis; Matsyakshi; beta sitosterol; HPTLC